British librarianship and information science : 1966-1970 - Whatley, H.A. (London : Library Association, 1972)
The book is divided into ten sections: 1. Libraries and the community. 2. Library Materials. 3. Bibliographic control. 4. Information. 5. Library building. 6. Management of libraries. 7. Profession of Librarianship. 8. Types of libraries. 9. Extension services and 10. Association.
Includes bibliographical references and index.
rpm 25/01/2019
Loans
Keywords: Library science; Libraries; Great Britain